A highly efficient 2D siloxene coated Ni foam catalyst for methane dry reforming and an effective approach to recycle the spent catalyst for energy storage applications. Issue 32 (29th July 2019) - Krishnamoorthy, Karthikeyan; M. S. P., Sudhakaran; Pazhamalai, Parthiban; Mariappan, Vimal Kumar; Mok, Young Sun; Kim, Sang-Jae
Abstract : An effective approach to reuse the carbon deposited spent catalyst (siloxene/Ni foam) after the methane dry reforming process is demonstrated by utilizing them as electrodes for supercapacitor devices. Abstract : The dry reforming of methane (DRM) using CO2 for the production of syngas (H2 and CO) has received increasing attention for reducing global CO2 emissions. The main drawback of DRM reactions is the limited reusability of the spent catalyst due to carbon deposition on its surface. Thus, designing an appropriate catalytic system is adequate to achieve increased syngas production with low carbon deposition, and developing smart strategies to reuse the carbon deposited spent catalyst is highly desirable. In this work, two dimensional siloxene sheet (silicon analog of graphene oxide) coated nickel foam is examined as a novel catalyst for the DRM reaction. The siloxene/Ni foam catalyst demonstrated superior catalytic performance in terms of conversion efficiencies (for CH4 and CO2 ) and syngas production (H2 and CO) with a high H2 /CO ratio of 1.5. Further, the carbon deposited siloxene/Ni spent catalyst recovered after the DRM reaction was effectively re-utilized as electrodes for a symmetric supercapacitor (SSC) using an organic electrolyte. The fabricated SSC (using the spent catalyst as electrodes) delivered a high device capacitance (24.65 F g −1 ), high energy density (30.81 Wh kg −1 ), and high-power density (15 625 W kg −1 ) with a long cycle life. Considering that the estimated carbon cost for developing a supercapacitor electrode is about 15 per kilogram, our strategy to effectively reutilize the recovered carbon deposited spent catalyst for energy storage applications might be a promising and economical approach for utilization of the spent catalyst.